Indicadores de desempenho como suporte a decisões operacionais no departamento comercial de uma empresa logística - Daleprani, Sidnei (2018)
Given the high competitiveness in logistic segment, making processes more efficient, recognizing market trends and competitive actions, modeling processes to make them more efficient, reducing operational problems to increase customer satisfaction with quality level and anticipating market trends and competitive actions are some of the key aspects to achieving and maintaining leadership in the parcel logistics business. The analysis of the processes involved seeks to understand the needs of the business, aiming to implement strategies to increase market intelligence and competitive advantage. With the support of indicators, managers and consultants can make more efficient decisions, aligned with company strategies, using up-to-date and accurate information. Therefore, we propose to improve the analysis of the business data of the organization studied, with the objective of providing qualified and reliable information for the management and decision making, to generate value with a focus on the needs of the clients. With the implementation of this solution, we envision optimizing business processes, improving results and developing the ability to respond quickly to market opportunities, threats and demands. These points are essential for the maintenance and expansion of business competitiveness in the competitive market of parcels transport.